Analysis Implementation of Marketing Mix in Asmorobangun Studio Art - Shofiyuddin, M. Alif (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research is a qualitative research to examine the Analysis of the Implementatioof Marketing Mix in Asmorobangun Studio Art. The focus of this study describes thimplementation of the marketing mix in the Asmorobangun Padepokan. The purpose of thistudy is to find out the various types of marketing mix strategy implementation which consistof determining the location, cost, price, promotion, product, people, process and physicaenvironment carried out by Asepobangun Padepokan to preserve Malang Dance and MasCulture. This study uses a qualitative approach to the case study method, the data analyzed ithe result of interviews with Padepokan Leaders, Padepokan Management, and consumers oAsmorobangun Padepokan. Direct observation of objects in the field and documentation breviewing research findings with marketing mix theory. The results showed that thimplementation of the marketing mix carried out by Asmorobangun Stuido Art was gooenough because its application was considered not too difficult and very acceptable to thcommunity. The marketing mix program implemented by the Asmorobangun Padepokan iconsidered to be very helpful in helping dance and mask Malang to the younger generation anhelping the economy of the local people.Keywords: Implementation, Marketing Mix, Asmorobangun Studio Art.